The Effectiveness of an Interactive Science E-Module Assisted Augmented Reality with a Contextual Teaching and Learning Approach in Enhancing Science Process Skills Among Elementary School Students - Kadek Hengki Primayana; Putu Yulia Angga Dewi (Universitas Pendidikan Ganesha, 2026)
The low level of science process skills among elementary school students and the limited use of interactive and contextual learning media in science education. This study aims to analyze the effectiveness of implementing an interactive science e-module assisted by Augmented Reality with a Contextual Teaching and Learning approach in improving students’ science process skills. This research uses a quantitative approach with a quasi-experimental method and a pretest posttest control group design. The research subjects consist of an experimental group and a control group involving elementary school students. Data collection was conducted through a science process skills test in the form of a questionnaire administered before and after the treatment. The research instrument was tested for validity and reliability. Data were analyzed using an independent t-test with the help of SPSS software. The results show a significant difference between the experimental and control groups, indicating that the interactive e-module assisted by Augmented Reality with a Contextual Teaching and Learning approach is more effective in improving students’ science process skills. The conclusion of this study shows that the integration of Augmented Reality technology and a contextual approach can create a more interactive, meaningful, and student centered learning process. The implication of this study is the importance of developing digital learning media to support 21st century skills, particularly science process skills.